HUBUNGAN PENYELESAIAN KONFLIK, BEBAN KERJA DAN KOMITMEN TERHADAP KEPUASAN KERJA PEGAWAI PADA RSUD PASAMAN BARAT - Azizah Azizah; Lendrawati Lendrawati (BADAN PENERBIT STIEPARI PRESS, 2022)
This study aims to determine Conflict Resolution, Workload and Commitment to Employee Job Satisfaction at West Pasaman Hospital. The method used is multiple linear regression analysis, by distributing a questionnaire of 64 respondents. The results showed that there was a positive and significant relationship between conflict resolution and job satisfaction at RSUD Pasaman Barat. There is a positive and significant relationship between workload and job satisfaction at RSUD Pasaman Barat. There is a positive and significant relationship between commitment and job satisfaction at RSUD Pasaman Barat. Conflict resolution, workload and commitment simultaneously have a positive and significant relationship with job satisfaction. The independent variable that has the greatest relationship with the dependent variable is conflict resolution. The contribution of conflict resolution variables, workload and commitment is 0.739 or 73.9% while the remaining 26.1% is influenced by other variables. Finally, the authors suggest to RSUD Pasaman Barat to further improve conflict resolution because conflict resolution has the greatest influence on job satisfaction of employees at RSUD Pasaman Barat.